Transcriptome Sequencing Reveals Regulatory Mechanisms of Taxol Synthesis in Taxus wallichiana var. Mairei - Tao Wang; Yiming Chen; Weibing Zhuang; Fengjiao Zhang; Xiaochun Shu; Zhong Wang; Qing Yang (International Journal of Genomics)
Taxol is one of the most potent and effective anticancer drugs and is originally isolated from Taxus species. To investigate the specific regulatory mechanisms of taxol synthesis in Taxus wallichiana var. mairei, RNA-seq was conducted to reveal the differences in transcriptional levels between wild type (WT) and “Jinxishan” (JXS), a cultivar selected from a population of Taxus mairei that shows about 3-fold higher taxol content in the needles than WT. Our results indicated that high expressions of the genes taxadienol acetyltransferase (TAT), taxadiene 5-alpha hydroxylase (T5H), 5-alpha-taxadienol-10-beta-hydroxylase (T10OH), and 2-debenzoyl-7,13-diacetylbaccatin III-2-O-benzoyl-transferase (DBBT), which catalyze a series of key acetylation and hydroxylation steps, are the main cause of high taxol content in JXS. Moreover, in the present study, the activation of jasmonic acid (JA) signal transduction and its crosstalk with gibberellin (GA), auxin, and ethylene (ET) explained the elevation of differentially expressed genes (DEGs) from the taxol biosynthesis pathway. This also indicates that taxol biosynthesis in T. mairei is associated with the balance of cell development and defense. TF-encoding (transcriptional factor) genes, represented by the ethylene-responsive transcription factor (ERF), basic/helix-loop-helix (bHLH), MYB, and WRKY families, were detected as differentially expressed between JXS and WT, further indicating that the regulation of hormone signaling on taxol biosynthesis genes was mediated by transcription factors (TFs). To our knowledge, this is the first study to illustrate the regulatory mechanisms of taxol synthesis in a new cultivar of T. mairei with a high taxol content in its needles. These transcriptome data provide reasonable explanations for the variation of taxol content between WT and JXS.